Kunjungan Wisatawan Dan Dampaknya Terhadap Pengangguran Terbuka Dan Pengentasan Kemiskinan - Dwiningwarni, Sayekti Suindyah; Suyanto, Suyanto; Andari, Syamsiyah Yuli Dwi (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
In Jombang Regency, the tourism sector is a new source of Regional Income (PAD), because in Jombang there are no Regional Regulations relating to tourism. So far, the management of the tourism sector is still haphazard, but the tourism sector has contributed to PAD. Apart from that, the tourism sector also contributes to reducing the number of poverty and alleviating poverty. However, during this pandemic, the contribution of the tourism sector to reducing poverty and alleviating poverty is very low, this is because many tourism sector businesses have been affected by the pandemic. Therefore, this research aims to analyze the impact of tourist visits on open unemployment and poverty alleviation. This research uses PATH Trimming model analysis with Natural Logarithmic Time Series data. The research results show that the results of sub-structure test 1 state that the results of testing hypothesis 1, which states that there is a negative and significant influence between the independent variable (X) on the endogenous (intervening) variable, are accepted. The results of testing sub structure 2 stated that the results of testing hypothesis 2, which stated that there was a positive and significant influence between the independent variable (X) on the endogenous (dependent) variable, were accepted. The results of hypothesis test 3, which stated that there was no negative and significant influence between the endogenous (intervening) variables Y1, Y2 and Y3 on the endogenous (dependent) variable Z1, were rejected. The results of sub-structure test 3 state that the results of hypothesis test 4 which states that there is a negative and significant influence between the independent variable (X) on the endogenous (dependent) variable Z2, are accepted. The results of hypothesis testing 5, stating that there is no negative and significant influence between the endogenous (dependent) variable Z1 on the endogenous (dependent) variable Z2, are rejected.